Characteristics Of Dyspepsia Patients Undergoing Endoscopy At Ibnu Sina Hospital Makassar - Muh Anugrah Ramadhan; Prema Hapsari Hidayati; Rachmat Faisal Syamsu; Asrini Safitri; Edward Pandu Wiriansya; Rahmawati, Rahmawati; Andi Muhammad Luthfi Parewangi (Jurnal EduHealth, 2024)
Background: According to the World Health Organization (WHO) that Indonesia ranks 3rd with the highest number of dyspepsia sufferers after America and England with 450 dyspepsia sufferers. According to the 2017 health data profile, dyspepsia is included in the top ten inpatient diseases.Objective: To determine the characteristics of dyspepsia patients undergoing endoscopy at the Ibnu Sina Hospital Makassar. Research methods: The research design used was descriptive research with a cross sectional approach using secondary data at the medical record installation at Ibnu Sina Hospital, Makassar. Research result: Of the 85 samples in the study, most were in the middle age of 45-54 years, namely 58 patients (68.2%), in the area of ​​origin the highest was the province of South Sulawesi, namely 80 patients (94%), the most gender was female, namely 38 patients (44.7%), the highest complaints were complaints (cough, tightness, and chest pain) namely 85 patients (100%), the largest laboratory results were laboratory results (hemoglobin, urea, SGOT and SGPT) namely 80 patients (80% ), the most common indication for endoscopy was chronic dyspepsia, namely 72 patients (84.7%), the most clinical diagnosis was functional dyspepsia, namely 32 patients (37%), the most endoscopy diagnosis was erosive gastritis, namely 38 patients (100%). Conclusion: Characteristics of patients with dyspepsia symptoms undergoing endoscopy at Ibn Sina Hospital Makassar, namely middle age, female sex, complaints of heartburn, endoscopy indications for chronic dyspepsia, clinical diagnosis of functional dyspepsia, and endoscopy diagnosis of erosive gastritis.